Índice de fundos de investimento em ações no Brasil: performance, apreçamento e previsão - Neri, Felipe Emerson Teixeira (2011)
This working paper investigates the performance of a theoretical value-weighted portfolio of stocks mutual funds through of the analysis of its performance by 10 years. This mechanism is interesting for evaluation of the performance of comparative mutual fund to some real benchmarks of the market (and sectors), also the Ibovespa, which was the inspiration for the elaboration of the theoretic metric. This study will make the evaluation of the main statistics of the used series as database and will serve for the formation of a Market Index of Stock Mutual Funds. The portfolio of 68 investment Brazilian stock mutual funds had been analyzed in the period between January of 1998 and December of 2009. It must be pointed out that the main objective of this work is not to prescribe a formula or alternative of investment, but to analyze the performance of the strategy that was adopted for the comment of some evidences.